High-Resolution Protein Interaction Map of the Drosophila melanogaster p38 Mitogen-Activated Protein Kinases Reveals Limited Functional Redundancy. - Belozerov, V.E.; Lin, Z.Y.; Gingras, A.C.; McDermott, J.C.; Michael Siu, K.W. (Molecular and Cellular Biology, 2012)
Functional redundancy is a pivotal mechanism that supports the robustness of biological systems at a molecular, cellular, and organismal level. The extensive prevalence of redundancy in molecular networks has been highlighted by recent systems biology studies; however, a detailed mechanistic understanding of redundant functions in specific signaling modules is often missing. We used affinity purification of protein complexes coupled to tandem mass spectrometry to generate a high-resolution protein interaction map of the three homologous p38 mitogen-activated protein kinases (MAPKs) in Drosophila and assessed the utility of such a map in defining the extent of common and unique functions. We found a correlation between the depth of integration of individual p38 kinases into the protein interaction network and their functional significance in cultured cells and in vivo. Based on these data, we propose a central role of p38b in the Drosophila p38 signaling module, with p38a and p38c playing more peripheral, auxiliary roles. We also present the first in vivo evidence demonstrating that an evolutionarily conserved complex of p38b with glycogen synthase links stress sensing to metabolic adaptation.